Pengaruh Terpaan Iklan Televisi dan Daya Tarik Celebrity Endorser dalam Kampanye #RambutAkuKataAku terhadap Keputusan Pemebelian Shampo Dove - Fidella Nala Sani; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Currently, the development of shampoo in Indonesia is increasingly diverse with a large variety of existing shampoos aimed to various groups. The shampoo sales market in Indonesia continues to develop, accompanied by the emergence of various new brands and new innovations. To keep improving and maintaining their shampoo products in the Indonesian market, Dove communicates their shampoo through the